Proton radiography of magnetic fields generated with an open-ended coil driven by high power laser pulses - Liao, Guoqian; Li, Yutong; Zhu, Baojun; Li, Yanfei; Li, Fang; Li, Mengchao; Wang, Xuan; Zhang, Zhe; He, Shukai; Wang, Weiwu; Lu, Feng; Zhang, Faqiang; et al. (Matter and radiation at extremes, 2016)
Recently generation of strong magnetic (B) fields has been demonstrated in capacitor coils heated by high power laser pulses [S. Fujioka et al., Sci. Rep. 3, 1170 (2013)]. This paper will present a direct measurement of B field generated with an open-ended coil target driven by a nanosecond laser pulse using ultrafast proton radiography. The radiographs are analyzed with particle-tracing simulations. The B field at the coil center is inferred to be ∼50 T at an irradiance of ∼5 × 1014 W·cm−2. The B field generation is attributed to the background cold electron flow pointing to the laser focal spot, where a target potential is induced due to the escape of energetic electrons.